Regional variation of bone density, microarchitectural parameters, and elastic moduli in the ultradistal tibia of young black and white men and women - Unnikrishnan, Ginu; Xu, Chun; Popp, Kristin L.; Hughes, Julie M.; Yuan, Amy; Guerriere, Katelyn I.; Caksa, Signe; Ackerman, Kathryn E.; Bouxsein, Mary L.; Reifman, Jaques (Bone (New York, N.Y.), 2018)
Whole-bone analyses can obscure regional heterogeneities in bone characteristics. Quantifying these heterogeneities might improve our understanding of the etiology of injuries, such as lower-extremity stress fractures. Here, we performed regional analyses of high-resolution peripheral quantitative computed tomography images of the ultradistal tibia in young, healthy subjects (age range, 18 to 30 years). We quantified bone characteristics across four regional sectors of the tibia for the following datasets: white women (n = 50), black women (n = 51), white men (n = 50), black men (n = 34), and all subjects (n = 185). After controlling for potentially confounding variables, we observed statistically significant variations in most of the characteristics across sectors (p < 0.05). Most of the bone characteristics followed a similar trend for all datasets but with different magnitudes. Regardless of race or sex, the anterior sector had the lowest trabecular and total volumetric bone mineral density and highest trabecular separation (p < 0.001), while cortical thickness was lowest in the medial sector (p < 0.05). Accordingly, the anterior sector also had the lowest elastic modulus in the anterior-posterior and superior-inferior directions (p < 0.001). In all sectors, the mean anisotropy was ~3, suggesting cross-sector similarity in the ratios of loading in these directions. In addition, the bone characteristics from regional and whole-bone analyses differed in all datasets (p < 0.05). Our findings on the heterogeneous nature of bone microarchitecture in the ultradistal tibia may reflect an adaptation of the bone to habitual loading conditions. •Regional analyses of bone characteristics of young, healthy subjects revealed significant differences across sectors.•The medial sector had the thinnest cortical bone in general and the lowest cortical density in women.•Total and trabecular bone mineral densities were lowest, and trabecular separation was highest, in the anterior sector.•Heterogeneity in tibial bone microstructure may reflect an adaptation to habitual loading conditions.